Hepatitis C Virus (HCV) Treatment With Directly Acting Agents Reduces the Risk of Incident Diabetes: Results From Electronically Retrieved Cohort of HCV Infected Veterans (ERCHIVES). (12th April 2019) - Butt, Adeel A; Yan, Peng; Aslam, Samia; Shaikh, Obaid S; Abou-Samra, Abdul-Badi
Abstract: Background: The effects of interferon-based therapies for hepatitis C virus (HCV) upon the risk of diabetes are controversial. The effects of newer, directly acting antiviral agents (DAA) upon this risk are unknown. We sought to determine the effects of HCV treatment upon the risk and incidence of diabetes. Methods: Using the Electronically Retrieved Cohort of HCV Infected Veterans (ERCHIVES) database for persons with chronic HCV infection (n = 242 680), we identified those treated with a pegylated interferon and ribavirin regimen (PEG/RBV, n = 4764) or a DAA-containing regimen (n = 21 279), after excluding those with diabetes at baseline, those with a human immunodeficiency virus or hepatitis B virus coinfection, and those treated with both PEG/RBV and DAA regimens. Age-, race-, sex-, and propensity score–matched controls (1:1) were also identified. Results: Diabetes incidence rates per 1000 person-years were 20.6 (95% confidence interval [CI] 19.6–21.6) among untreated persons, 19.8 (95% CI 18.3–21.4) among those treated with PEG/RBV, and 9.89 (95% CI 8.7–11.1) among DAA-treated persons ( P < .001). Among the treated, rates were 13.3 (95% CI 12.2–14.5) for those with a sustained virologic response (SVR) and 19.2 (95% CI 17.4–21.1) for those without an SVR ( P < .0001). A larger reduction was observed in persons with more advanced fibrosis/cirrhosis (absolute difference 2.9 for fibrosis severity score [FIB-4] < 1.25; 5.7 for FIB-4 1.26–3.25; 9.8 for FIB-4 >3.25). DAA treatment (hazard ratio [HR] 0.53, 95% CI .46–.63) and SVR (HR 0.81, 95% CI .70–.93) were associated with a significantly reduced risk of diabetes. DAA-treated persons had longer diabetes-free survival rates, compared to untreated and PEG/RBV-treated persons. There was no significant difference in diabetes-free survival rates between untreated and PEG/RBV-treated persons. The results were similar in inverse probability of treatment and censoring weight models. Conclusions: DAA therapy significantly reduces the incidence and risk of subsequent diabetes. Treatment benefits are more pronounced in persons with more advanced liver fibrosis. Abstract : In a large cohort of patients with hepatitis C virus, the incidence and risk of subsequent diabetes was significantly lower for those using directly acting antiviral agents therapy. Treatment benefits were more pronounced in persons with more advanced liver fibrosis.